Vertical control of civil infrastructure, using terrestrial lidar and classic topography - V. Vargas, Esteban (2025)
The civil works may be subject to vertical or horizontal displacements due natural causes, deformations or human factors, so it is important ensure that the structures are within the design parameters form an accurate field check and the respective analysis to determine corrective measures to mitigate or remedy possible impacts on the infrastructure. In the present study case, the verticality of the structure was controlled, to verify its verticality and determine the existence of displacements, taking into consideration the recommendations of the Manual de Carreteras, Caminos y Puentes CR-2010. For this purpose, two measurement methodologies are used together, the first one based in the utilization of the Terrestrial LiDAR and the last one using conventional surveying, linked through the establishment of a local reference polygonal applying the Bessel method with complete series, ensuring the connection between the information obtain through both techniques, and subsequently detecting movements greater than those recommended by regulations. In addition, the data obtain with Terrestrial LiDAR is validated, thereby obtaining a model of the structure under study, serves as a reference for the application of conventional surveying in interest areas and perform the analysis of the information more efficiently and quickly, also ensuring the quality of the data obtain in the vertical control. The methodology proposed validate the use of Terrestrial LiDAR from the comparison with instruments and methodologies recognized in the control of civil works, also allows the detection of displacements through a precise integration of the reference data obtained from the point cloud and the accuracy of the total station for specific verifications. This approach provides continuous monitoring of infrastructures, reducing analysis time and ensuring data quality, making it a fundamental tool for project management.